2012
DOI: 10.1108/17561371211224764
|View full text |Cite
|
Sign up to set email alerts
|

The effects of medical insurance on durables consumption in rural China

Abstract: PurposeThe New Rural Cooperative Medical Scheme (NRCMS), implemented in China since 2003, has greatly increased the access of the poor to health services and alleviated the hardship caused by catastrophic medical payments. Both the precautionary saving theory and the Buffer‐Stock saving theory would predict a positive effect of this event on consumption. The purpose of this paper is to empirically study the effects of medical insurance on durables consumption in rural China.Design/methodology/approachUsing Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
(15 reference statements)
1
10
0
Order By: Relevance
“…Exploiting the longitudinal structure of the CHNS data, our triple-difference analysis uses two pre-NCMS datasets (collected in 2000 and 2004) to estimate and then control for differences in the time trends of health outcomes between the treatment and comparison groups in the absence of the NCMS. Our analysis suggests that the double-difference method adopted in most previous studies 8,16,18,19,[21][22][23] underestimates the impacts of the NCMS on incidences of chronic diseases among the elderly. Correcting potential biases in the doubledifference estimates, our triple-difference estimates (some combined with propensity score matching) indicate that among the elderly, the NCMS reduced the incidences of apoplexy and diabetes by 3-6 and 3-4 percentage points, respectively.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…Exploiting the longitudinal structure of the CHNS data, our triple-difference analysis uses two pre-NCMS datasets (collected in 2000 and 2004) to estimate and then control for differences in the time trends of health outcomes between the treatment and comparison groups in the absence of the NCMS. Our analysis suggests that the double-difference method adopted in most previous studies 8,16,18,19,[21][22][23] underestimates the impacts of the NCMS on incidences of chronic diseases among the elderly. Correcting potential biases in the doubledifference estimates, our triple-difference estimates (some combined with propensity score matching) indicate that among the elderly, the NCMS reduced the incidences of apoplexy and diabetes by 3-6 and 3-4 percentage points, respectively.…”
Section: Introductionmentioning
confidence: 69%
“…Somewhat counterintuitive, Lei and Lin (2009) 16 found that while the NCMS significantly increased utilization of preventive care, it did not improve the insureds' health outcomes. This lack of conclusive evidence is particularly puzzling given the findings of significant impacts of the NCMS on outcomes that are not highly health-related, such as durable/nondurable consumption, [17][18][19] selfemployment, 20 daily activities and cognitive function, 21 and child education. 22 In any case, these inconclusive findings render it difficult to derive useful lessons and policy recommendations regarding how the program can be further improved to achieve better population health outcomes or population well-being in other dimensions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A related study found that consumption of durables such as washing machines and color TVs was positively related to the number and proportion of rural households with health insurance. 38 But not all studies support the hypothesis that wider and deeper health insurance increases consumer spending. 39 , 40 The low level of consumption in China’s economy impacts savings, and inclusion of this can yield different results.…”
Section: Health Spending and Macroeconomicsmentioning
confidence: 99%
“…Gan, Yin and Zang (2010) investigate how the privatization of public housing in the 1990s influenced durable consumption in urban China. Ying and Du (2012) document that rural households with medical insurance are more likely to adopt durables. However, local spillovers in the diffusion of durables are rarely examined.…”
Section: Introductionmentioning
confidence: 99%